Robot Assisted Bladder Diverticulectomy Seven Year After Radical Prostatectomy - Asher Mandel; Kaushik Prabhav Kolanukuduru; Manish Kumar Choudhary; Swati Bhardwaj; Vinayak Wagaskar; Avinash Reddy; Ash Tewari (Journal of Urological Surgery, 2025)
The impact of radical prostatectomy on the natural history of the neurogenic bladder is not well understood. Neurogenic bladder can manifest as detrusor sphincter dyssynergia. When left untreated, neurogenic bladder can cause bladder hypotonia. Chronically high volumes and pressures can result in the formation of bladder diverticula. Diverticula, if present, are usually located at the lateral walls of the bladder. In this case, a 77-year-old man with a neurogenic bladder presented with a symptomatic bladder diverticulum at the dome, which developed years after radical prostatectomy. A complex history made him a candidate for definitive treatment; thus, a diverticulectomy was performed. The history and operative and pathological findings are discussed.